Insulin-related traits and prostate cancer: A Mendelian randomization study - Chen, Guihua; Wang, Yi; Wang, Xiang (Computational and structural biotechnology journal, 2024)
Investigating the causal relationship between insulin secretion and prostate cancer (PCa) development is challenging due to the multifactorial nature of PCa, which complicates the isolation of the specific impact of insulin-related factors. We conducted a Mendelian randomization (MR) study to investigate the associations between insulin secretion-related traits and PCa. We used 36, 60, 56, 23, 48, and 49 single nucleotide polymorphisms (SNPs) as instrumental variables for fasting insulin, insulin sensitivity, proinsulin, and proinsulin in nondiabetic individuals, individuals with diabetes, and individuals receiving exogenous insulin, respectively. These SNPs were selected from various genome-wide association studies. To clarify the causal relationship between insulin-related traits and PCa, we utilized a multivariable MR analysis to adjust for obesity and body fat percentage. Additionally, two-step Mendelian randomization was conducted to assess the role of insulin-like growth factor 1 (IGF-1) in the relationship between proinsulin and PCa. Two-sample MR analysis revealed strong associations between genetically predicted fasting insulin, insulin sensitivity, proinsulin, and proinsulin in nondiabetic individuals and the development of PCa. After adjustment for obesity and body fat percentage using multivariable MR analysis, proinsulin remained significantly associated with PCa, whereas other factors were not. Furthermore, two-step MR analysis demonstrated that proinsulin acts as a negative factor in prostate carcinogenesis, largely independent of IGF-1. This study provides evidence suggesting that proinsulin may act as a negative factor contributing to the development of PCa. Novel therapies targeting proinsulin may have potential benefits for PCa patients, potentially reducing the need for unnecessary surgical treatments. [Display omitted] •We conducted the first Mendelian randomization (MR) study on the insulin secretion-related traits and prostate cance.•Two-sample MR analysis revealed a positive association between insulin sensitivity and the risk of prostate cancer.•After adjustment through multivariable MR analysis, proinsulin remained significantly associated with prostate cancer.•Two-step MR analysis indicates that IGF-1 mediates the causal relationship between proinsulin and prostate carcinogenesis.•Our results suggest that proinsulin may act as a risk factor contributing to the development of prostate cancer.